Critical security methods : new frameworks for analysis - Aradau, Claudia, 1976- (Abingdon, Oxon : Routledge, 2014)
'Critical Security Methods offers a new approach to research methods in critical security studies. It argues that methods are not simply tools to bridge the gap between security theory and security practice. Rather, to practice methods critically means engaging in a more free and experimental interplay between theory, methods and practice. This recognises that the security practices we research are often methods in their own right, as forms of surveillance, data mining, visualisation, and so on, and that our own research methods are themselves practices that intervene and interfere in those sites of security and insecurity. Against the familiar methdological language of rigour, detachment and procedural consistency, Critical Security Methods reclaims the idea of method as experiment. The chapters offer a series of methodological experimentations that assemble concepts, theory and empirical cases into new frameworks for critical security research. They show how critical engagement and methodological innovation can be practiced as interventions into diverse instances of insecurity and securitisation, including airports, drug trafficking, peasant struggles, biometrics and police kettling. The book will be a valuable resource for students and researchers in critical security studies, politics and international relations'--
Includes bibliographical references and index.
Keywords: Security, International; International relations